Low Temperature Stress Mediates the Antioxidants Pool and Chlorophyll Fluorescence in Vitis vinifera L. Cultivars - Mohammad A. Aazami; Majid Asghari-Aruq; Mohammad B. Hassanpouraghdam; Sezai Ercisli; Mojmir Baron; Jiri Sochor (Plants, 2021)
Grapes are sensitive to early autumn and spring low temperature damage. The current study aimed to assay the effects of cold stress (+1 °C for 4, 8, and 16 h) on three grapevine cultivars (Ghiziluzum, Khalili, and Perllete). The results showed that cold stress caused significant changes in the antioxidant and biochemicals content in the studied cultivars. Furthermore, examining the chlorophyll fluorescence indices, cold stress caused a significant increase in minimal fluorescence (F0), a decrease in maximal fluorescence (Fm), and the maximum photochemical quantum yield of photosystem II (Fv/Fm) in all cultivars. Among the studied cultivars, ‘Perllete’ had the highest increase in proline content and activity of antioxidant enzymes and also had the lowest accumulation of malondialdehyde, hydrogen peroxide, electrolyte leakage, and F0, as well as less of a decrease in Fm and Fv/Fm, and had a higher tolerance to cold stress than ‘Ghiziluzum’ and ‘Khalili’. ‘Perllete’ and ‘Ghiziluzum’ showed reasonable tolerance to the low temperature stress. ‘Khalili’ was sensitive to the stress. The rapid screening of grapevine cultivars in early spring low temperatures is applicable with the assaying of some biomolecules and chlorophyll fluorescence.